Hubungan Peran Pengawas Menelan Obat (PMO) dan Kepatuhan Pasien Menelan Obat dengan Kejadian TBC MDR - Novie Mauliku; Dyan Nugraeheni; Teguh Akbar Budiana; Elis Rosita (Universitas Jenderal Achmad Yani Yogyakarta, 2022)
Background: Tuberculosis (TBC) until now still a public health problem, Indonesia take second position with highest TBC MDRload in the world. Tle level of TBC MDR treatment success in Indonesia on 2013 reach 51% despite Tuberculosis handling effort with DOTS strategy has been applied since 1995. One of DOTS strategy component is direct supervision swallowing drug by supervisory role o swallowing drug to prevent drug resistance.Objective: research is to know the related of supervisory role and patient compliance swallowing drug with incidence of MDR tuberculosiMethods: Research desain using case control. The sample case is target total population 15 peoples and control sample is TBC patient with drug sensitive 30 peoples. Data analysis is univariat analysis, bivariate using Chi SquareResults: shows there is a relationship between supervisory role of swallowing drug with TBC MDR p value=0,034; OR = 9,3 (95% CI: 1,080-80,627) and patient compliance swallowing drug p value=0,015; OR = 6,4 (95% CI: 1,606-25,644) with TBC MDRConclusion: PMO monitoring and medication adherence are associated with the incidence of MDR. Recommend to public health service place for intensity increase of TBC MDR patient home visit about the importance supervisory role and patient compliance swallowing drug